Kyrgyz Republic : School Autonomy and Accountability - World Bank (Washington, DC, 2014)
The Kyrgyz Republic is in a state of educational transition. Its process of reform is aimed at improving education quality by increasing the quality of its teachers, reducing inequity in education finance, and updating its curriculum and instructional materials. Improving school autonomy and accountability are two of the main recommendations made by recent analysis. Therefore, the benchmarking of these two issues is timely. Budgetary autonomy is emerging; local governments are free to assign the budget to schools but lack mechanisms to improve budgetary efficiency and equity. Personnel autonomy is latent, with district-level offices of the Ministry of education and science being in charge of teacher selection under a central pay scale. Education in the Kyrgyz Republic is regulated by the National Education Law of 1992, amended in 2003. Teachers and preschool education are managed under separate laws. There are five indicators of school autonomy and accountability that can help benchmark an education system's policies that enable school autonomy and accountability: school autonomy in budget planning and approval; school autonomy in personnel management; the participation of the school council in school finance; the assessment of school and student performance; and school accountability to stakeholders. This report focuses specifically on policies in the area of school autonomy and accountability.